Numerical simulation of water droplet impact test on aircraft wing structure. (August 2019) - Manigandan, S.; Dineshkumar; Ramanathan, Muthiaya; Gunasekar, P.; Devipriya, J.; Nithya, S.; Gokulnath, R.
Abstract: The three-dimensional simulation is carried out to study the collision dynamics of the water droplets impinging on the aircraft structures at higher velocities. The composite wing made of hybrid fiber of combination, Kevlar-Glass with nanocomposite graphene (5 sheets of kevlar and 3 Sheets of glass). Meanwhile, the fibers are fabricated using vacuum bagging process. In addition to the epoxy, the catalyst and the nanoparticle added to the resin to increase the strength of the laminates. The water droplet model is designed using Smoothed-particle hydrodynamics (SPH) modelling with the aid of Navier Stokes equation. Furthermore, the water is impinged using an elliptical spray nozzle at a constant height of 100m. For feasibility, the small part of the composite wing structure is exposed to the impact of water droplet at different velocity ranges from 0 to 40m/s. Subsequently, the behaviour of the droplet is studied for three various crosswind effects of 15m/s and 25m/s. From the results, it is clear that the stress and strain are depending on the impact velocity of the droplets. On the contrary, the damage is very little which does not cause any deformation or failure of the structure of the airplane. The numerical observations results are in reasonable and acceptable.